1974
DOI: 10.3758/bf03199196
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in rats’ spontaneous alternation

Abstract: Fifteen-day-old rats made random choices in a T-maze, while adult levels of alternation (approximately 70%) were noted among 30-day-olds, Also, younger pups were insensitive to a lengthening of the intertrial interval, unlike older animals whose rate of alternation decreased when a l-h delay was interposed between arm entries, These findings are consistent with the hypothesis that hippocampal development is a factor in the ontogeny of postweaning locomotion. The unsystematic pattern of goal-arm selections amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…When short delays were interposed between the forced and choice runs in the spatial alternation task, 20‐day‐old pups made more errors than 40‐ and 60‐day‐old pups. This initial improvement in the spatial performance, comprised between 20 and 40 days after birth, coincides with evidence from other behavioral studies which also shown the appearance of spatial working memory in rats between 20 and 30 days after birth (Bronstein et al, 1974; Brown et al, 2005; Castro et al, 1987; Green & Stanton, 1989). Further changes in pups' spatial performance were also observed when longer intervals (10 min) were inserted between runs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…When short delays were interposed between the forced and choice runs in the spatial alternation task, 20‐day‐old pups made more errors than 40‐ and 60‐day‐old pups. This initial improvement in the spatial performance, comprised between 20 and 40 days after birth, coincides with evidence from other behavioral studies which also shown the appearance of spatial working memory in rats between 20 and 30 days after birth (Bronstein et al, 1974; Brown et al, 2005; Castro et al, 1987; Green & Stanton, 1989). Further changes in pups' spatial performance were also observed when longer intervals (10 min) were inserted between runs.…”
Section: Discussionsupporting
confidence: 88%
“…The late development of the hippocampus is reflected in the age‐dependent emergence of spatial memory observed in various rodent species. First works showed that while 15‐day‐old pup's rats made random choices in a T‐maze, adult levels of correct choices of 70% were observed among 30‐day‐old pups (Bronstein, Dworkin, & Bilder, 1974). Similarly, Castro, Paylor, and Rudy (1987) and Green and Stanton (1989) found ontogenetic differences in the development of short‐memory in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies of the possibility that the persistently active juvenile rat is exploring its environment disconfirmed the hypothesis, however. Two-weekold pups do not exhibit spontaneous alternation in a T maze (e.g., Bronstein, Dworkin, & Bilder, 1974), a response often used to signify exploration in rodents. Furthermore, Palese and Bronstein (1976) persistently active juveniles would not pattern their movements any differently than older animals when tested in a cross maze.…”
mentioning
confidence: 99%
“…No significant Trial 1 directional preferences were found. Alternation behavior did not consistently increase with age as expected (Bronstein et al, 1974;Douglas et al, 1973;Egger et al, 1973). However, whereas 17-day-old animals showed perserverative behavior or alternated at chance levels, 37-day-old animals in 5 of the 6 groups were alternating a t a reliable rate of approximately 65%.…”
Section: Spontaneous A1 Ternationmentioning
confidence: 73%
“…Spontaneous motor activity (SMA) and spontaneous alternation (SA) were used to assess disruptions in behavioral ontogeny following prenatal treatment-exposure of the pregnant female to electric foot shock-as both of these behaviors show distinct developmental patterns (Bronstein, Dworkin, & Bilder, 1974;Campbell, Lytle, & Fibiger, 1969;Douglas, Peterson, & Douglas, 1073;Egger, 1973a,b;Pappas, Peters, Sobrian, Blouin, & Drew, 1975;Sobrian, Weltman, & Pappas, 1975) and have been linked to the development of serotonergic, cholinergic, and noradrenergic systems in the brain (Egger, Livesey, & Dawson, 1973;Swonger & Rech, 1972;Trimbach, 1972). The development of reflexes, physical features, and body weight were evaluated t o determine the extent to which somatic systems were affected.…”
Section: Sobrianmentioning
confidence: 99%